Perfil metabólico e hormonal de vacas 1/2, 3/4 e >7/8 Holandês-Gir sob mesmo sistema de produção durante o período pré e pós-parto - Ana Paula Saldanha Franzoni (2016)
Although brazilian herd is mainly composed of crossbred cows, the nutritional and reproductive management systems are based on survey data with herds of animals Bos taurus, mainly Holstein, with little knowledge about the incidence and characterization of diseases in peri-partum mainly related to specific crosses F1 and 3/4 Holstein-Gyr. This study aimed to characterize the effect of genetic composition in body condition, milk yield, metabolic and hormone profile of crossbred cows 1/2, 3/4 and > 7/8 (7/8 HG, 15/16 HG and Holstein) Holstein-Gir on a single farm, under the same management during the pre and post-partum period. 28 multiparous cows - 1/2 HG (n = 8) 3 / 4HG (n = 10) and> 7/8 Holstein (n = 10) were used. Data statistical analysis was performed by dividing samplings into periods: prepartum (nine, seven and five days prepartum); first month postpartum (between 3 and 28 postpartum); second month postpartum (between 28 and 63 days postpartum). All genetic groups showed typical estimated lactation curves. The total milk production and duration of lactation were greater for groups 3/4HG (1955,64L and 7924.92 ± 324.4 ± 97.9 days) and >7/8HG (6934.85 ± 2038,74L and 345.3 ± 36.4 days) compared to group 1/2HG (3968.64 ± 2795,76L and 231.0 ± 105.5 days) (p <0.05). The milk production peak was higher for group 3/4HG (31.3 ± 2,9L) compared to cows 1/2HG (21.2 ± 9,1L) (p <0.05) and genetic group 7/8HG (28.4 ± 3,6L) was similar to the other two groups (p> 0.05). The time to reach peak production in days did not differ between groups (p> 0.05) (1/2HG: 60,5±25,4; 3/4HG: 45,5±12,3; >7/8HG: 63,4±27,5). Cows 1/2HG had higher BCS at calving (3.9 ± 0.3) and greater loss of BCS postpartum (0.6 ± 0.2) (p <0.05). There was no difference between genetic groups for the time in days to reach the lowest BCS from the partum (1/2HG: 13,0±10,6; 3/4HG: 6,6±7,0; >7/8HG: 7,1±9,1), days to the BCS recovery from partum (1/2HG: 24,8±14,1; 3/4HG: 12,6±13,9; >7/8HG: 20,4±23,2), BCS in the week of first ovulation (1/2HG: 3,5±0,4; 3/4HG: 3,2±0,3; >7/8HG: 3,3±0,3), weeks to first ovulation (1/2HG: 5,3±2,3; 3/4HG: 3,7±1,6; >7/8HG: 3,9±1,6) and period of servisse (1/2HG: 110,3±54,1; 3/4HG: 125,0±41,7; >7/8HG: 154,1±91,9) (p> 0.05). There were no differences in the plasma levels of NEFA between genetic groups or in the weeks evaluated (p> 0.05), and the values were below 0.123 mmol/L in all experimental periods regardless of genetic group. In the prepartum period, the plasma glucose concentration was higher for the genetic group 1/2HG (59.7 ± 3.7 mg/dL) (p<0.05) and plasma insulin concentration of genetic group 3/4HG (9.5 ± 2.9 U/mL) was similar to groups1/2HG (8.7 ± 2.8 U/mL) and >7/8HG (6.9 ± 2.1 U/mL) (p > 0.05). The plasma concentrations of IGF-1 was similar between the 3/4HG group (189.3 ± 42.5 ng/mL) and other genetic groups (p>0.05), however the group 1/2HG (213, 9 ± 40.0 ng/mL) values were higher than the group >7/8HG (168.4 ± 29.3 ng/mL) (p <0.05). In the first month postpartum, there were no differences in plasma concentrations of insulin, glucose and IGF-1 (p> 0.05) from different genetic groups. In the second month postpartum, genetic group 3/4HG (57.5 ± 7.7 mg/dL) had plasma concentrations of glucose similar to groups 1/2HG (63.0 ± 6.4 mg/dL) and >7/8 GH (56.5 ± 4.7 mg / dL). However, the 1/2 HG group showed higher concentrations than the group > 7/8 HG (p <0.05). The plasma insulin concentration was higher for the genetic group 1/2HG (22.1 ± 18.9 U/mL) compared to groups 3/4HG (9.9 ± 4.4 U / ml) and >7/8HG (8.9 ± 4.0 U/mL) (p <0.05). The 1/2HG cows showed higher plasma concentrations of IGF-1 (288.1 ± 117.5 ng/mL) in the same period (p <0.05). There were differences in the metabolic and hormonal profile between genetic groups and 3/4 HG group showed greater adaptability to the experimental conditions.